2021
DOI: 10.1371/journal.pone.0244119
|View full text |Cite
|
Sign up to set email alerts
|

High real-time reporting of domestic and wild animal diseases following rollout of mobile phone reporting system in Kenya

Abstract: Background To improve early detection of emerging infectious diseases in sub-Saharan Africa (SSA), many of them zoonotic, numerous electronic animal disease-reporting systems have been piloted but not implemented because of cost, lack of user friendliness, and data insecurity. In Kenya, we developed and rolled out an open-source mobile phone-based domestic and wild animal disease reporting system and collected data over two years to investigate its robustness and ability to track disease trends. Methods The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Mobile-phone-based syndromic surveillance of people and animals in remote rural areas could overcome barriers related to remoteness and guide veterinary and public health services. Kenya has deployed an integrated human and animal syndromic surveillance system, the Kenya Animal Biosurveillance System (KABS), 29 which targets disease syndromes prioritised by national health agencies, allowing health data from across the country to be rapidly transferred to health authorities. However, because KABS does not connect beyond clinically trained health-care professionals, its reach within remote rural areas is currently limited.…”
Section: How Can We Do Better?mentioning
confidence: 99%
“…Mobile-phone-based syndromic surveillance of people and animals in remote rural areas could overcome barriers related to remoteness and guide veterinary and public health services. Kenya has deployed an integrated human and animal syndromic surveillance system, the Kenya Animal Biosurveillance System (KABS), 29 which targets disease syndromes prioritised by national health agencies, allowing health data from across the country to be rapidly transferred to health authorities. However, because KABS does not connect beyond clinically trained health-care professionals, its reach within remote rural areas is currently limited.…”
Section: How Can We Do Better?mentioning
confidence: 99%
“…While the standard field disease surveillance report from the Notifiable Disease-1 (ND-1) form in Kenya does not provide syndromic data, our abortion burden estimates correlated with data collected using an open-source animal disease reporting system that used mobile phones in collecting data for over two years in other parts of the country [ 15 ]. This study, therefore, showcased the underestimation surrounding the ’true’ incidence of abortion rates estimated using the manual surveillance systems in the country.…”
Section: Discussionmentioning
confidence: 89%
“…In response to this, we previously undertook two surveillance studies that demonstrated gaps and burden of livestock abortions—an active RVF surveillance effort where we found that livestock abortions accounted for 37% of the reported RVF-associated syndromes [ 14 ]. Our other study that used an open-source mobile phone-based disease reporting system among domestic and wild animals revealed a high frequency of livestock abortions exceeded only by respiratory, gastrointestinal and skin diseases [ 15 ]. Notably, these and other existing data on livestock abortion in Kenya has focused on specific diseases, locations, or species.…”
Section: Introductionmentioning
confidence: 99%
“…Reluctance to report ASF due to fear of consequences like quarantine and movement bans is not uncommon [ 7 ], but in many instances, reporting is simply too difficult. The advent of mobile phones and their wide usage in Africa has greatly facilitated communication [ 6 , 83 , 84 , 85 ], but information as to who to inform may not be available in areas that are poorly served in terms of animal health. Clear lines of communication need to be established between pig keepers and other value chain actors and the veterinary services [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%